Ultrathin MWCNT/Ti3C2Tx Hybrid Films for Electromagnetic Interference Shielding - Chuanxin Weng; Junzhe He; Jiangxiao Tian; Wei Wu; Jinjin Li; Jiulin Zhang; Haitao Yu; Xuechuan Zhang; Mingming Lu (Nanomaterials)
The disordered assembly and low conductivity of carbon nanotubes are the main problems that limit the application of electromagnetic interference (EMI) shielding. In this work, an ordered lamellar assembly structure of multiwalled carbon nanotube/Ti3C2Tx (MWCNT/Ti3C2Tx) hybrid films was achieved by vacuum-assisted filtration through the hybridization of Ti3C2Tx nanosheets and carbon nanotubes, where carbon nanotubes were tightly sticking on the surface of Ti3C2Tx nanosheets via physical adsorption and hydrogen bonding. Compared with the pure carbon nanotubes films, the hybrid MWCNT/Ti3C2Tx films achieved a significant improvement in conductivity of 452.5 S/cm and EMI shielding effectiveness (SE) of 44.3 dB under 50 wt% Ti3C2Tx with a low thickness (8.6 μm) and orderly lamellar stacking structure, which finally resulted in high specific SE (SSE/t, SE divided by the density and thickness) of 55,603.1 dB∙cm2∙g−1.